Resilience moderates the association between stigma and psychological distress among family caregivers of patients with schizophrenia. (July 2016) - Chen, Xiaoyun; Mao, Yixuan; Kong, Linghua; Li, Guopeng; Xin, Minglan; Lou, Fenglan; Li, Ping
Abstract: The aims of this study were to describe the prevalence of psychological distress, to further validate the influence of caregivers' stigma and resilience on their psychological distress, and to explore the moderating effect of resilience in the relationship between stigma and psychological distress in caregivers. Participants were 125 family caregivers of individuals with schizophrenia from one provincial Mental Health Center in China. The Kessler Psychological Distress Scale (K10), Perceived Devaluation and Discrimination Scale (PDD) and the Ten-item Connor-Davidson Resilience Scale (CD-RISC10) were used to measure their psychological distress, stigma, and resilience, respectively. A total of 33.6% of caregivers had high levels of psychological distress. Lower levels of resilience and higher levels of stigma among caregivers contributed to greater psychological distress. Furthermore, the moderating effect of resilience in the relationship between stigma and psychological distress in family caregivers of patients with schizophrenia was firstly verified. This study also highlighted that intervention to promote resilience, especially in caregivers who had higher levels of stigma, might be helpful to alleviate their psychological distress. Highlights: Caregivers of patients with schizophrenia had a high level of psychological distress in China. Family caregivers' resilience and stigma have a direct effect on their psychological distress. Resilience moderated the effects of stigma on psychological distress.